2013
DOI: 10.18676/cadernoscenpec.v3i1.205
|View full text |Cite
|
Sign up to set email alerts
|

Fracasso escolar: evolução das oportunidades educacionais de estudantes de diferentes grupos raciais

Abstract: Este trabalho foi apresentado na 36º Reunião Anual da Anped em Goiânia (GO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
0
1
0
21
Order By: Relevance
“…Pesquisadores afirmam que há associação entre fracasso escolar e algumas características dos alunos, entre elas sua origem social e racial (ALVES; ORTIGÃO; FRANCO, 2007;MACHADO;GONZAGA, 2007;LOUZANO, 2013). Para Souza et al (2010),os altos índices de reprovação são entrave à universalização do acesso e da conclusão na idade adequada do ensino médio no Brasil e constitui problema antigo da educação nacional.…”
Section: Crenças De Professores E Reprovação Escolarunclassified
“…Pesquisadores afirmam que há associação entre fracasso escolar e algumas características dos alunos, entre elas sua origem social e racial (ALVES; ORTIGÃO; FRANCO, 2007;MACHADO;GONZAGA, 2007;LOUZANO, 2013). Para Souza et al (2010),os altos índices de reprovação são entrave à universalização do acesso e da conclusão na idade adequada do ensino médio no Brasil e constitui problema antigo da educação nacional.…”
Section: Crenças De Professores E Reprovação Escolarunclassified
“…In the international literature, researchers have been engaged in investigating teachers' expectations as a possible mechanism by which performance inequalities between students from major or minority social groups, men and women, and students from more or less affluent families, can emerge and grow (TIMMERMANS, DE BOER, VAN DER WERF, 2016). Although national studies that specifically address the influence of school or class racial profiling on teacher expectations are not known, recent analyses have identified racial discrepancies in the probability of success in schools (LOUZANO, 2013) and in student assessment (GOIS, 2009), as well as socioeconomic differentials in teachers' expectations (INSTITUTO AYRTON SENNA, 2015). Research with public schools in Belo Horizonte, Brazil found different educational expectations according to gender, but not according to the students' skin color (BARBOSA; RANDALL, 2006).…”
Section: He Existence Of Socio-demographic Differentials In Educationmentioning
confidence: 99%
“…A desigualdade escolar por sua vez gera o fracasso escolar. Louzano, (2013), o considera um fenômeno complexo relacionado às oportunidades educacionais desiguais que afeta de forma diferente alunos de distintos grupos econômicos, sociais e étnico-raciais.…”
Section: Silva (2006) Também Concorda Com Estudo Deunclassified